THE ROLE OF TEACHERS IN USING THE MEDIA PICTURE READING CARDS TO IMPROVE READING ABILITY - Meriana, Meriana; Pangestu, Widya Trio; Khusniyah, Tri Wardati (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The ability to read is very important in supporting education, the teacher’s role in this case is to improve students’ ability to understand science through reading. Picture reading cards are one of several media that can be used to improve students’ reading skills. The goal of this research is to describe the role of the teacher in the use of illustrated reading card media to improve the reading ability of class 1 students at Madrasah Ibtidaiyah Pesantren Sabilil Muttaqien Hargomulyo, as well as to identify the obstacles and how to overcome them. Along with a case study, the descriptive qualitative research method was applied. This research focuses on the usage of picture reading card media. The data for this study were collected through observing, interviewing, and documenting the class 1 homeroom and class 1 pupils of Madrasah Ibtidaiyah Pesantren Sabilil Muttaqien Hargomulyo, as well as by library research. Data reduction, data presentation, generating conclusions, and data verification are all part of the researcher’s data analysis efforts. To validate data, researchers employ the triangulation approach (combined). When picture reading cards were used, the data demonstrated that the teacher’s role had a good effect on students’ reading skills.